2022
DOI: 10.1007/s13753-022-00441-2
|View full text |Cite
|
Sign up to set email alerts
|

Induced Earthquake Hazard by Geothermal Power Plants: Statistical Evaluation and Probabilistic Modeling

Abstract: This study statistically evaluated the characteristics of induced earthquakes by geothermal power plants (GPPs) and generated a probabilistic model for simulating stochastic seismic events. Four well-known power plant zones were selected worldwide from the United States, Germany, France, and New Zealand. The operational condition information, as well as the corresponding earthquake catalogs recorded in the vicinity of GPPs, were gathered from their commencement date. The statistical properties of events were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It represents the structure of facial changes as a linear combination of local basis functions whose coefficients are proportional to the brightness intensity of the pixels. This research showed that a linear model with Gabor fuzzy shift could calculate the linear functions based on the framework [22,23]. The proposed method uses video images as training and test data.…”
Section: Introductionmentioning
confidence: 99%
“…It represents the structure of facial changes as a linear combination of local basis functions whose coefficients are proportional to the brightness intensity of the pixels. This research showed that a linear model with Gabor fuzzy shift could calculate the linear functions based on the framework [22,23]. The proposed method uses video images as training and test data.…”
Section: Introductionmentioning
confidence: 99%